2018
DOI: 10.1021/acsami.8b15951
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Periodic Surface Structures (LIPSS) on Heavily Boron-Doped Diamond for Electrode Applications

Abstract: Diamond is known as a promising electrode material in the fields of cell stimulation, energy storage (e.g., supercapacitors), (bio)sensing, catalysis, etc. However, engineering its surface and electrochemical properties often requires costly and complex procedures with addition of foreign material (e.g., carbon nanotube or polymer) scaffolds or cleanroom processing. In this work, we demonstrate a novel approach using laser-induced periodic surface structuring (LIPSS) as a scalable, versatile, and cost-effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 64 publications
(115 reference statements)
1
30
0
1
Order By: Relevance
“…Moreover, the width of ripples becomes narrower and longer, which is in line with the previous results found by A.F. Sartori et al [29]. It has also been observed that a large number of melt slags showed up in the irradiated region.…”
Section: Influence Of Effective Number Of Pulses On Cvd Diamond Coatisupporting
confidence: 92%
“…Moreover, the width of ripples becomes narrower and longer, which is in line with the previous results found by A.F. Sartori et al [29]. It has also been observed that a large number of melt slags showed up in the irradiated region.…”
Section: Influence Of Effective Number Of Pulses On Cvd Diamond Coatisupporting
confidence: 92%
“…Laser ablation offers a versatile platform that can simultaneously induce surface structures [1][2][3] and synthesize nanomaterials [4][5][6][7][8][9][10][11][12][13] for diverse applications, such as wettability control [14][15][16][17] , bioimaging 6,18 , cellular growth manipulation [19][20][21] , lithium-ion batteries 22 , surface enhanced Ra-man scattering (SERS) detection 23,24 , catalysis/ photocatalysis/electrochemical-catalysis 6,7,25 and antifriction [26][27][28][29] . Laser processing also enables the microfabrication of three-dimensional structures and devices 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Diamond is considered a promising electrode material in the fields of cell stimulation, energy storage, (bio) sensing, and catalysis. In 2018, A. F. Sartori et al reported an integrated characterization of the electrochemical and morphological/structural properties of laser-induced periodic surface structures (LIPSS) formed on heavily boron-doped CVD diamond (BDD) [301]. The vertical step between each horizontal grid line was set to 100 µm to align the ablated regions.…”
Section: Carbon Materialsmentioning
confidence: 99%